ANALYSIS OF ADVERTISING INFLUENCE, BRAND TRUST, AND INSTAGRAM PRODUCT REVIEWS ON THE PURCHASE DECISION OF SKINTIFIC SKINCARE - Moch Yusuf Haidar Ali Ramdhani; Fikih Abdul M; M. Ferdy Irzami; Salman Al Farisi Sentika; Syti Sarah Maesaroh (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2024)
Objective – This research aims to analyze how much influence the use of Instagram by Skintific on consumer purchase decisions. Design/Methodology/Approach – The research method used is quantitative with a survey design. The sample was taken randomly from as many as 101 respondents from various regions in Tasikmalaya. The analysis was performed using SPSS software version 27.0. Findings – The study's findings indicate that advertising, brand trust, and product reviews have a significant positive impact on the decision to purchase Skintific skincare products through Instagram in the Tasikmalaya region. Conclusion and Implications – The strategy of using social media Instagram was able to bring Skintific to be known very widely. Once consumers get to know a brand, then direct them to explore and observe product reviews from other consumers. Then consumers will judge the products they buy to create brand trust in Skintific skincare products.